Investigation of the In Vitro Antioxidant Potential Of Polyphenolic-Rich Extract of Lam Stem Bark and Its Antidiabetic Activity In Streptozotocin-Induced Diabetic Rats - Basiru Olaitan Ajiboye PhD; Oluwafemi Adeleke Ojo PhD; Babatunji Emmanuel Oyinloye PhD; Mary Abiola Okesola MSc; Adeyonu Oluwatosin BSc; Aline Augusti Boligon PhD; Abidemi Paul Kappo PhD (SAGE Publishing, 2020)
Artocarpus heterophyllus Lam (Moraceae) stem bark has been used locally in managing diabetes mellitus with sparse scientific information. This study investigates the in vitro antioxidant potential of polyphenolic-rich extract of A heterophyllus stem bark as well as its antidiabetic activity in streptozotocin-induced diabetic rats. Fifty male Wistar rats were used with the induction of diabetes by a single intraperitoneal injection of streptozotocin (45 mg/kg body weight) and were orally administered 400 mg/kg free and bound phenols of A heterophyllus stem bark. The animals were sacrificed on the 28th day of the experiment using the cervical dislocation method; antihyperglycemia and anti-inflammatory parameters were subsequently assessed. The polyphenolic extracts demonstrated antioxidant potentials (such as hydrogen peroxide and diphenyl-1-picrylhydrazyl), as well as strong inhibitory activity against amylase and glucosidase. There was a significant ( P < .05) increase in glycogen, insulin concentration, pancreatic β-cell scores (HOMA-β), antioxidant enzymes and hexokinase activities, as well as glucose transporter concentration in diabetic animals administered the extracts and metformin. Also, a significant ( P < .05) reduction in fasting blood glucose, lipid peroxidation, glucose-6-phosphatase, and all anti-inflammatory parameters were observed in diabetic rats administered the extracts and metformin. The extracts demonstrated antidiabetic potential, which may be useful in the management of diabetes mellitus